La responsabilité historique de Vera Feyder - Zbierska-Mościcka, Judyta (Studia Romanica Posnaniensia, 2016)
In her writing, Vera Feyder, representative of the tribe called by the historians of Belgian iterature generation of identity, the question of identity is inextricably linked with the experience of World War II. The memory of childhood marked by the martyrdom of his father and the deep misery and loneliness, in which the author and his mother lived in the wartime, decide on the content and meaning of her writing. A sense of responsibility for other people, all resistance to the injustice, disagreement with indifference, memory of the past – it is a kind of code, which, according to Feyder, should apply a modern writer.